Polystichum dongchuanense and P. menglaense (subg. Haplopolystichum; Dryopteridaceae), two new ferns from Yunnan, China - Liang, Zhen-Long; He, Zhao-Rong; Zhang, Li-Bing (Phytotaxa, 2021)
Two new fern species, Polystichum dongchuanense and P. menglaense (Dryopteridaceae), are described and illustrated from Yunnan, China. Both are members of P. subg. Haplopolystichum sect. Haplopolystichum. Polystichum dongchuanense is most similar to P. acutidens in plant size and pinna size, but the two can be distinguished from each other by pinna serration and soral number on pinnae. Polystichum menglaense is most similar to P. deltodon in plant size, but the two are different in pinna shape and soral distribution. Both new species have extremely narrow distributions and are classified as Critically Endangered (CR) following IUCN Red List Criteria.